2018
DOI: 10.1186/s40359-018-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between parent and child report of physical activity, sedentary and dietary behaviours in 9-12-year-old children and associations with children’s weight status

Abstract: BackgroundTo date, population based surveys aimed at gaining insight in health related behaviour of children have often used either child self-reports or parent proxy reports. It remains unclear however, if surveys using different sources of information from either parents or children are comparable. In addition, (over)weight status of children can lead to under- and over reporting by parents and children as a result of social desirability bias. We aimed at gaining insight in the level of agreement between par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…With respect to children's diet, the amount of parent-child agreement has been shown to differ depending on the type of food assessed, with low agreement for the consumption of fruits and vegetables [5][6][7], but slightly higher agreement for sweetened beverages [7,8], and moderate agreement for the consumption of fish, eggs, and fast food [7]. Regarding aspects of eating culture, e.g., having breakfast or sharing dinners, agreement between child and parent reports has been shown to be low to fair [9]. In a study that compared dietary reports completed by 8-to 11-year-old children and their parents with energy expenditure as measured by the doubly labeled water technique revealed that child reports were more accurate than parent reports [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to children's diet, the amount of parent-child agreement has been shown to differ depending on the type of food assessed, with low agreement for the consumption of fruits and vegetables [5][6][7], but slightly higher agreement for sweetened beverages [7,8], and moderate agreement for the consumption of fish, eggs, and fast food [7]. Regarding aspects of eating culture, e.g., having breakfast or sharing dinners, agreement between child and parent reports has been shown to be low to fair [9]. In a study that compared dietary reports completed by 8-to 11-year-old children and their parents with energy expenditure as measured by the doubly labeled water technique revealed that child reports were more accurate than parent reports [10].…”
Section: Introductionmentioning
confidence: 99%
“…Parents, especially mothers, have been shown to overestimate the energy intake of their children [10]. Regarding physical activity or outdoor play, agreement between child and parent reports has been reported to be fair [9,11]. Interestingly, agreement has been shown to be higher for organized than for non-organized physical activity [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias was high in most studies, which was, to a large part, due to measurement of outcomes. Retrospective report, which was most commonly used in the studies included in this review, is considered to be imprecise because of poor recall and (parents of) children with low levels of water consumption reporting higher amounts than actual amounts consumed . For our meta‐analysis, we estimated water consumption in millilitres per day for studies that did not report water consumption in volume per day by using a serving size of 225 mL.…”
Section: Discussionmentioning
confidence: 99%